Intersectionality in Digital Games: an analysis of the games Celeste and GTA San Andreas (Simbiótica. Revista Eletrônica, 2025)
Understanding digital games as mediatic devices that produce knowledge through multiple power relations, this study seeks to trace how the tool of intersectionality guides the production of digital games, based on the analysis of Celeste and Grand Theft Auto: San Andreas. We opted for a content analysis of game elements (characters, narratives, and contexts), observing the intersection of oppression categories, agencies, and forms of resistance that shape the analyzed games' content. The analysis of Celeste reveals how Madeline’s struggle reflects the complex interactions between gender identity, mental health, and social marginalization, highlighting the internal and external challenges faced by transgender people. In GTA: San Andreas, the intersections shape CJ’s experiences and reflect the social realities of discrimination and oppression portrayed in the game.
Keywords: digital games; Intersectionality; gender; race